When the menorah fades - Preigerzon, Zvi, 1900-1969 (Cherry Orchard Books, an imprint of Academic Studies Press, 2020)
"Zvi Preigerzon (1900-1969), a Hebrew writer in the Soviet Union, wrote this book in complete secrecy, to the extent that he even hid its existence from his own family. The book is about the Jewish community in Hadiach, a small town in Ukraine where Shneur Zalman Schneerson, the founder of the Chabad movement, is buried. The town was occupied by the German army during the war and most of its Jewish population perished. Zvi Preigerzon describes the life of the simple Jewish people and their suffering under the Nazis, with a Kabbalistic spiritual touch: the Perpetual Flame of the Menorah at the grave of Shneur Zalman Schneerson symbolizes the very spirit of Jewish life, which it is said will persist as long as the flame is burning"--